A Study on Prescribing Adherence for Surgical Antibiotic Prophylaxis Protocol in a Rural Hospital in India - A, Jeewan; T, Dixon; DS, Alexander; G, Alvarez-Uria (Indian Journal of Pharmacy Practice)
Background: There is an increasing concern about the spread of antimicrobial resistance among hospitalized patients due to the inadequate use of antibiotics. Surgical antibiotic prophlylaxis (SAP) protocols are useful for rationalizing the use of antibiotics while surgical interventions. The objective of this study was to evaluate the adherence to a protocol for surgical prophylaxis at a Surgical Department in a rural district hospital in South India. Methodology: It's a retrospective observational study conducted for a period of 6 months (July to December 2011). Terminally ill and immunocompromised patients were not included in the study. Result& Discussion: A total of 512 cases were screened. The overall adherence rate to the hospital protocol was 39.84%. Maximum adherence scores were found in cholelithiasis (100%) and hernia (98.4) surgeries, and minimum adherence scores were found in appendicular (5.26%) and urological (13.3%) surgeries. Adherence to protocol was higher for children and lower for older patients. Conclusion: Adherence to the SAP protocol was low, suggesting more studies to find out the reasons for fewer adherences. The challenges of infections are much higher in rural population with less sanitization and lack of awareness. It was also recommended to revise the protocols as per local needs.
Keywords: Surgical protocol; protocol adherence; surgical prophylaxis; antibiotics; prescribers